Neutrophil–lymphocyte ratio predicts cardiovascular and all-cause mortality in hemodialysis patients. (2nd January 2016) - Neuen, Brendon L.; Leather, Nicole; Greenwood, Alice M.; Gunnarsson, Ronny; Cho, Yeoungjee; Mantha, Murty L.
Abstract: Neutrophil–lymphocyte ratio (NLR) is a marker of systemic inflammation that has been shown to predict mortality in patients with malignancies, ischemic heart disease and peripheral vascular disease. Its prognostic value in hemodialysis patients is unclear. The aims of this study were to: (i) explore the relationship between NLR and other biochemical parameters and (ii) to examine the value of NLR as a predictor of cardiovascular and all-cause mortality in hemodialysis patients. The study included all the incident hemodialysis patients from a single center between 2007 and 2012. NLR was calculated using samples obtained 3 months after commencing hemodialysis. One hundred seventy hemodialysis patients were included with a median follow-up of 37 months. There were 54 deaths (32%). NLR was positively correlated with C-reactive protein ( r = 0.24, p = 0.0023) and negatively correlated with hemoglobin ( r = −0.27, p = 0.00048), albumin ( r = −0.23, p = 0.0034) and total cholesterol ( r = −0.17, p = 0.049) levels. In multivariate Cox regression, NLR was independently associated with both all-cause mortality (adjusted hazard ratio [HR] 1.4; 95% confidence interval [CI], 1.2–1.6; p ≤ 0.0001) and cardiovascular death (HR 1.3, 95% CI 1.1–1.6, p = 0.0032). Other predictors of all-cause mortality were age (HR 1.6 per decade; 95% CI, 1.2–2.1; p = 0.0017), body mass index (HR 0.93; 95% CI, 0.88–0.98; p = 0.0047), albumin (HR 0.91; 95% CI, 0.86–0.97; p = 0.0035) and peripheral vascular disease (HR 2.7; 95% CI, 1.4–5.1; p = 0.0023). NLR is a practical, cost-efficient and easy to use predictor of cardiovascular and all-cause mortality in incident hemodialysis patients.